2015
DOI: 10.1002/bkcs.10300
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the Crystallinity of MgZnO with a Zn Buffer Layer by Sol–Gel Spin‐coating Method

Abstract: We fabricate magnesium zinc oxide (MZO) thin films inserting a buffer layer between a film and a substrate with different annealing temperatures. The structural and optical properties of MZO thin films are investigated by using scanning electron microscopy, X-ray diffraction (XRD), and photoluminescence. The XRD patterns for the buffer layers annealed at 200 C show the narrowest full width at half maximum and the most intense (0 0 2) diffraction peak. In addition, the buffer layers decrease the magnitude of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…[ 34 ] This result is further supported by the narrower full‐width at half‐maximum (FWHM) of the first GIXD peak. [ 35 ] The FWHM values in the out‐of‐plane direction in the as‐cast, annealed at 240 °C, and annealed at 300 °C films were 0.056, 0.038, and 0.050, respectively. The crystallographic analysis revealed that the PDPADPP polymer film annealed at 240 °C had more extensive long‐range intermolecular interactions and an optimal crystal structure for OFET devices.…”
Section: Resultsmentioning
confidence: 99%
“…[ 34 ] This result is further supported by the narrower full‐width at half‐maximum (FWHM) of the first GIXD peak. [ 35 ] The FWHM values in the out‐of‐plane direction in the as‐cast, annealed at 240 °C, and annealed at 300 °C films were 0.056, 0.038, and 0.050, respectively. The crystallographic analysis revealed that the PDPADPP polymer film annealed at 240 °C had more extensive long‐range intermolecular interactions and an optimal crystal structure for OFET devices.…”
Section: Resultsmentioning
confidence: 99%